Cancer Cell-Derived Exosomes Promote HCC Tumorigenesis Through Hedgehog Pathway - Li, Li; Zhao, Jing; Zhang, Quanbao; Tao, Yifeng; Shen, Conghuan; Li, Ruidong; Ma, Zhengyu; Li, Jianhua; Wang, Zhengxin (Frontiers in Oncology, 2021)
Purpose Hepatocellular carcinoma (HCC) accounts for more than 80% of primary liver cancers and is one of the leading causes of cancer-related death in many countries. Cancer cell-derived exosomes are shown to mediate communications between cancer cells and the microenvironment, promoting tumorigenesis. Hedgehog signaling pathway plays important roles in cancer development of HCC. Methods Exosomes were isolated from culture medium of HCC cell lines PLC/PRF/5 and MHCC-97H and were found to promote cancer cell growth measured with cell proliferation and colony formation assay. HCC cells cultured with cancer cell-derived exosome had increased cancer stem cell (CSC) population demonstrated by increased cell sphere formation CSC marker expressions. Hedgehog protein Shh was found to be highly expressed in these two HCC cell lines and preferably carried by exosomes. When Shh was knocked down with shRNA, the resulting exosomes had a reduced effect on promoting cancer cell growth or CSC population increase compared to normal cell-derived exosomes. Results The ability of PLC/PRF/5 cells to form tumor in a xenograft model was increased by the addition of the exosomes from control cancer cells but not the exosomes from Shh knocked down cancer cells. Finally, the higher plasma Exo-Shh levels were associated with later tumor stages, higher histological grades, multiple tumors, and higher recurrence rates. Conclusion This study demonstrated that HCC cells secreted Shh via exosome and promote tumorigenesis through the activated Hedgehog pathway.